Dynamic capabilities and internationalization of authentic firms: Role of heritage assets, administrative heritage, and signature processes - Arikan, Ilgaz; Koparan, Ipek; Arikan, Asli M; Shenkar, Oded (Journal of International Business Studies, 2022)
We study MNEs that tie their long-lasting competitiveness and internationalization to the deployment of their heritage assets, administrative heritage, and signature processes built in their home markets. When faced with changes, these “authentic” firms scan for and buffer against threats to their signature processes, use their heritage endowment to focus on their capacity to maintain and defend their niches, and preserve their capacity for stability. We complement the traditional dynamic capabilities perspective by redefining its boundary conditions. Furthermore, authentic firms resist and limit local adaptation of process and products, and internationalize only if opportune by deploying preservation capabilities.